Hyaluronic acid composition having penetration enhancing effect, preparation method and use thereof
Patent Information
- Application Number
- JP2023528565
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-11
- Filing Date
- 2021-11-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-11-05
AI Technical Summary
【0017】 1)本発明の浸透促進作用を有するヒアルロン酸又はその塩の組成物は、少ない添加量で処方中の他の有効成分の吸収を効果的に促進し、相乗効果を得ることができる。 2)本発明の浸透促進作用を有するヒアルロン酸又はその塩の組成物は、粒子径が小さく均一で、溶解速度が速く、製品において吸収速度に優れ、簡便な混合方式により処理されるヒアルロン酸よりも皮膚の水和度の向上に優れている。 3)本発明の浸透促進作用を有するヒアルロン酸又はその塩の組成物は、従来の浸透促進剤に比べて皮膚へのダメージがなく安全である。
Smart Images

Figure 0007646000000014 
Figure 0007646000000015 
Figure 0007646000000016
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of hyaluronic acid, in particular to a hyaluronic acid composition having penetration enhancing activity, a method for preparing the same and its use. [Background technology]
[0002] Since ancient times, loving beauty has been an ageless pursuit of people, especially women, and as we age, dull skin, dryness, sagging skin, wrinkles, etc., trouble everyone. Therefore, most young people realize that in order to maintain youthful features such as skin moisture, whiteness, firmness, and water-oil balance, they should take care of their skin early to slow down the aging process of their skin.
[0003] The skin is the largest organ in the human body, with an average adult skin surface area of approximately 1.6 m 2 Its total weight accounts for about 16% of body weight. From the outside to the inside, the skin is divided into three parts: the epidermis, the dermis and the subcutaneous tissue. The skin is not only an outer garment that decorates the human body, but also has a strong protective function. The brick-wall-like structure of the epidermis allows the skin to block foreign substances from the outside and protect the human body.
[0004] On the other hand, in order to rejuvenate the skin, the active substances in the skin care products must reach the target phase of the skin in order to function, so in the field of skin care products, it is important to promote the absorption of nutritional ingredients.
[0005] In the field of pharmaceutical development, formulators commonly use propanediol, azone, menthol, borneol, etc. as penetration enhancers to promote drug absorption and exert local therapeutic effects, but since pharmaceuticals are only used when there is an illness and are generally used locally, they do not take into consideration side effects such as sensitivity, redness, etc. Since cosmetics are preparations that are used every day, morning and night, there is a particular demand for penetration enhancers that are safe for the skin.
[0006] MB Brown et al. (European Academy of Dermatology and Venereology, 2005:19,308-318) used sodium hyaluronate as a drug matrix and found that HA significantly enhanced the distribution of diclofenac sodium through each layer of the skin, retaining and localizing the drug in the epidermal layer, compared to water, chondroitin sulfate, and sodium carboxymethylcellulose. The concentration of HA in this experiment was 2.5%.
[0007] In patent application CN202010407830.1 concerning a composition containing hyaluronic acid and polyhydric alcohol and its use, the present inventors disclose a composition of hyaluronic acid and polyhydric alcohol, which can improve the percutaneous absorption of water-soluble amino acid components, and allow the components to penetrate the epidermis and dermis without the use of a device, and provide effects and exert cosmetic effects, and the composition is composed of high molecular weight, low molecular weight and oligopolyhyaluronic acid or its salt, and a polyol-based antioxidant, and has a relatively complex composition.
[0008] However, to date, there have been no reports of simply using a hyaluronic acid composition to promote the production of a target active substance. Summary of the Invention
[0009] In response to the actual needs of developing skin care products and the problems existing in the current penetration enhancing system, the present invention effectively increases the transdermal absorption rate of the target active substance by using a combination of hydrolyzed hyaluronic acid or its salt, hyaluronic acid or its salt, and acetylated hyaluronic acid or its salt in the formulation. [Means for solving the problem]
[0010] The specific technical solutions of the present invention are as follows:
[0011] 1. Hyaluronic acid or a salt thereof; Acetylated hyaluronic acid or a salt thereof; A hyaluronic acid composition comprising hydrolyzed hyaluronic acid or a salt thereof. 2. The hyaluronic acid composition according to item 1, comprising hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof. 3. For hyaluronic acid compositions, The hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight. The acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight. Item 3. The hyaluronic acid composition according to item 1 or 2, wherein the hydrolyzed hyaluronic acid or a salt thereof is present in an amount of 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight. 4. The molecular weight of the hyaluronic acid or a salt thereof is 100 kDa to 500 kDa, preferably 150 kDa to 300 kDa, and more preferably 210 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or a salt thereof is 10 kDa to 100 kDa, preferably 10 kDa to 50 kDa, and more preferably 20 kDa to 30 kDa. Item 4. The hyaluronic acid composition according to any one of Items 1 to 3, wherein the molecular weight of the hydrolyzed hyaluronic acid or a salt thereof is 0.8 kDa to 20 kDa, preferably 3 kDa to 15 kDa, and more preferably 3 kDa to 10 kDa. 5. The composition according to any one of items 1 to 4, wherein the acetyl content of the acetylated hyaluronic acid or a salt thereof is 20 to 30 wt %.
[0012] 6. Dissolving hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof to obtain a solution; and spray drying the resulting solution to obtain a hyaluronic acid composition. 7. The method according to item 6, wherein the total amount of the hyaluronic acid or a salt thereof, the acetylated hyaluronic acid or a salt thereof, and the hydrolyzed hyaluronic acid or a salt thereof is 1 to 10% by mass relative to the solution. 8. The method according to item 6 or 7, wherein in the spray drying, the inlet temperature is 120 to 150° C., the outlet temperature is 80 to 100° C., and the atomization frequency is preferably 30 to 50 Hz. 9. For hyaluronic acid compositions, The hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight. The acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight. Item 9. The method according to any one of Items 6 to 8, wherein the hydrolyzed hyaluronic acid or a salt thereof is present at 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight. 10. The molecular weight of the hyaluronic acid or a salt thereof is 100 kDa to 500 kDa, preferably 150 kDa to 300 kDa, and more preferably 210 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or a salt thereof is 10 kDa to 100 kDa, preferably 10 kDa to 50 kDa, and more preferably 20 kDa to 30 kDa. Item 10. The method according to any one of Items 6 to 9, wherein the molecular weight of the hydrolyzed hyaluronic acid or a salt thereof is 0.8 kDa to 20 kDa, preferably 3 kDa to 15 kDa, and more preferably 3 kDa to 10 kDa. 11. The method according to any one of items 6 to 10, wherein the acetyl content of the acetylated hyaluronic acid or a salt thereof is 20% to 30%.
[0013] 12. A composition for promoting absorption of an active ingredient, the composition comprising the active ingredient and a hyaluronic acid composition described in any one of items 1 to 5 or a hyaluronic acid composition prepared by the preparation method described in any one of items 6 to 11. 13. The composition according to item 12, wherein the water-soluble active ingredient is tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene, or ectoine, and the oil-soluble active ingredient is astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoyl phenylalanine, or ethylbisiminomethylguaiacol manganese chloride. 14. The composition described in item 12 or 13, wherein the mass ratio of the active ingredient to the hyaluronic acid composition is 1:5 to 5:1, preferably 1:4 to 4:1.
[0014] 15. Use of the hyaluronic acid composition according to any one of items 1 to 5 or the hyaluronic acid composition prepared by the preparation method according to any one of items 6 to 11 in improving absorption of an active ingredient, preferably, the active ingredient is a water-soluble active ingredient and / or an oil-soluble active ingredient. 16. The use according to Item 15, wherein the water-soluble active ingredient is tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene, or ectoine, and the oil-soluble active ingredient is astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoyl phenylalanine, or ethylbisiminomethylguaiacol manganese chloride.
[0015] 17. A product comprising the composition according to any one of items 12 to 14. 18. The product according to item 17, wherein the hyaluronic acid composition is present in an amount of 0.1 to 2% by mass, preferably 0.5 to 1.5% by mass, relative to the mass of the product. 19. The product according to paragraph 17 or 18, wherein the product is a skin care product, a disinfectant product, a medicine, a dressing, or a gel medical device. 20. The product of paragraph 19, wherein the skin care product is a toner, essence, cream, mask or lotion.
[0016] 21. Use of the hyaluronic acid composition according to any one of items 1 to 5 or the hyaluronic acid composition prepared by the preparation method according to any one of items 6 to 11 in the field of products, preferably in an amount of 0.1 to 2% by weight, preferably 0.5 to 1.5% by weight, of the product. 22. The use according to item 21, wherein the product is a skin care product, a disinfectant product, a medicine, a dressing, or a gel medical device. Effect of the Invention
[0017] 1) The composition of the present invention containing hyaluronic acid or a salt thereof having a penetration enhancing effect can effectively promote the absorption of other active ingredients in the formulation even with a small amount added, thereby achieving a synergistic effect. 2) The composition of hyaluronic acid or its salt having the penetration enhancing effect of the present invention has a small and uniform particle size, a fast dissolution rate, and an excellent absorption rate in the product, and is superior in improving the hydration of the skin compared to hyaluronic acid processed by a simple mixing method. 3) The composition of the present invention containing hyaluronic acid or a salt thereof having a penetration enhancing effect is safer and causes less damage to the skin than conventional penetration enhancers. [Brief description of the drawings]
[0018] [Figure 1] 1 is a linear equation for tranexamic acid in Application Verification Example 1. [Diagram 2] This is a schematic diagram of the cumulative permeation amount of tranexamic acid per unit area when an in vitro permeation experiment is conducted using the hyaluronic acid composition obtained in Example 6 and a control product in Application Verification Example 1. [Diagram 3] FIG. 2 is a schematic diagram showing the amount of tranexamic acid retained in the skin at each time point when an experiment is conducted in Application Verification Example 1 using the hyaluronic acid composition obtained in Example 6. [Figure 4] 1 is a linear equation for astaxanthin in application verification example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will now be described in detail with reference to embodiments illustrated in the drawings, where like numerals represent like features in all drawings. Although specific examples of the invention are illustrated, it should be understood that the invention is not limited to the examples set forth herein, but may be embodied in various forms. Rather, these examples are provided to provide a more complete understanding of the invention, and to fully convey the scope of the invention to those skilled in the art.
[0020] In addition, in the specification and claims, several terms are used to refer to specific components. Those skilled in the art will understand that the same components may be referred to by different nouns. In the specification and claims, the difference in nouns is not used as a method of dividing components, but rather the functional difference of components is used as a basis for division. The terms "including" and "including" used throughout the specification and claims are open terms and should be interpreted as "including, but not limited to". In this specification, a preferred embodiment for carrying out the present invention is described, but the description is not intended to limit the scope of the present invention, but is intended for the general principles of the specification. The scope of protection of the present invention shall be as defined by the appended claims.
[0021] The present invention provides a hyaluronic acid composition comprising hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof.
[0022] The acetylated hyaluronic acid or a salt thereof is obtained by an acetylation reaction of hyaluronic acid or a salt thereof, and the introduction of acetyl gives the acetylated hyaluronic acid or a salt thereof lipophilicity.
[0023] The hydrolyzed hyaluronic acid or its salt is an oligohyaluronic acid or its salt produced by an enzymatic decomposition technique, which has a small molecular weight and is easily absorbed into the epidermis or dermis via the skin.
[0024] In a preferred specific embodiment of the present invention, in the hyaluronic acid composition, the hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight, the acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight, and the hydrolyzed hyaluronic acid or a salt thereof is 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight.
[0025] For example, in the hyaluronic acid composition, the content of the hyaluronic acid or a salt thereof may be 20% by weight, 25% by weight, 30% by weight, 35% by weight, 40% by weight, 45% by weight, 50% by weight, 55% by weight, 60% by weight, or any range therebetween. The acetylated hyaluronic acid or salt thereof may be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% by weight or any range therebetween, The hydrolyzed hyaluronic acid or salt thereof may be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% by weight or any range therebetween.
[0026] In a preferred specific embodiment of the present invention, the molecular weight of the hyaluronic acid or its salt is 100k to 500kDa, preferably 150k to 300kDa, and more preferably 210k to 300kDa, the molecular weight of the acetylated hyaluronic acid or its salt is 10k to 100kDa, preferably 10k to 50kDa, and more preferably 20k to 30kDa, and the molecular weight of the hydrolyzed hyaluronic acid or its salt is 0.8k to 20kDa, preferably 3k to 15kDa, and more preferably 3k to 10kDa.
[0027] For example, the molecular weight of the hyaluronic acid or salt thereof may be 100 kDa, 110 kDa, 120 kDa, 130 kDa, 140 kDa, 150 kDa, 160 kDa, 170 kDa, 180 kDa, 190 kDa, 200 kDa, 210 kDa, 220 kDa, 230 kDa, 240 kDa, 250 kDa, 260 kDa, 270 kDa, 280 kDa, 290 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, or any range therebetween; The molecular weight of the acetylated hyaluronic acid or salt thereof may be 10 kDa, 20 kDa, 30 kDa, 40 kDa, 50 kDa, 60 kDa, 70 kDa, 80 kDa, 90 kDa, 100 kDa or any range therebetween; The molecular weight of the hydrolyzed hyaluronic acid or salt thereof may be 0.8 kDa, 0.9 kDa, 1 kDa, 2 kDa, 3 kDa, 4 kDa, 5 kDa, 6 kDa, 7 kDa, 8 kDa, 9 kDa, 10 kDa, 11 kDa, 12 kDa, 13 kDa, 14 kDa, 15 kDa, 16 kDa, 17 kDa, 18 kDa, 19 kDa, 20 kDa or any range therebetween.
[0028] In a preferred specific embodiment of the present invention, the acetyl content of the acetylated hyaluronic acid or salt thereof is 20-30 wt %.
[0029] For example, the acetyl content of the acetylated hyaluronic acid or salt thereof can be, for example, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, or any range therebetween.
[0030] In certain preferred embodiments of the present invention, the hyaluronic acid composition consists of hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof.
[0031] The hyaluronate, acetylated hyaluronate or hydrolyzed hyaluronate is a metal ion salt, such as a sodium salt, a potassium salt, a calcium salt or a zinc salt, and is generally a sodium salt.
[0032] In a preferred embodiment of the present invention, the hyaluronic acid composition comprises hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof, In the hyaluronic acid composition, The hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight. The acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight. The content of the hydrolyzed hyaluronic acid or a salt thereof is 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight.
[0033] In a preferred embodiment of the present invention, the hyaluronic acid composition comprises hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof, In the hyaluronic acid composition, The hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight. The acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight. The hydrolyzed hyaluronic acid or a salt thereof is 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight, The molecular weight of the hyaluronic acid or a salt thereof is 100 kDa to 500 kDa, preferably 150 kDa to 300 kDa, and more preferably 210 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or a salt thereof is 10 kDa to 100 kDa, preferably 10 kDa to 50 kDa, and more preferably 20 kDa to 30 kDa. The molecular weight of the hydrolyzed hyaluronic acid or a salt thereof is 0.8 kDa to 20 kDa, preferably 3 kDa to 15 kDa, and more preferably 3 kDa to 10 kDa.
[0034] In a preferred embodiment of the present invention, the hyaluronic acid composition comprises hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof, As a weight percentage in the hyaluronic acid composition, The hyaluronic acid or a salt thereof is 20 to 60% by weight, preferably 25 to 55% by weight, and more preferably 25 to 40% by weight. The acetylated hyaluronic acid or a salt thereof is 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 35% by weight. The hydrolyzed hyaluronic acid or a salt thereof is 30 to 70% by weight, preferably 30 to 60% by weight, and more preferably 40 to 55% by weight, The molecular weight of the hyaluronic acid or a salt thereof is 100 kDa to 500 kDa, preferably 150 kDa to 300 kDa, and more preferably 210 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or a salt thereof is 10 kDa to 100 kDa, preferably 10 kDa to 50 kDa, and more preferably 20 kDa to 30 kDa. The molecular weight of the hydrolyzed hyaluronic acid or a salt thereof is 0.8 kDa to 20 kDa, preferably 3 kDa to 15 kDa, and more preferably 3 kDa to 10 kDa, and the acetyl content of the acetylated hyaluronic acid or a salt thereof is 20 to 30 wt %.
[0035] The mechanism of action of the hyaluronic acid composition of the present invention is estimated as follows: hyaluronic acid or its salt corresponds to a very small network structure, and is distributed on the surface layer of the skin; acetylated hyaluronic acid or its salt has acetyl group, so it has lipophilicity and affinity with skin, and can form a channel; hydrolyzed hyaluronic acid or its salt can penetrate quickly to the skin layer through the channel of acetylated hyaluronic acid or its salt; hydrolyzed hyaluronic acid or its salt can be mixed with hyaluronic acid or its salt to quickly open the barrier of the skin, and nutrients, hydrolyzed hyaluronic acid or its salt and nutrients combined with hyaluronic acid or its salt can enter the skin, promoting the absorption of active molecules, such as the absorption of oil-soluble active ingredients and water-soluble active ingredients in skin care products, and promoting the absorption of other active ingredients in disinfection products, medicines, dressings or gel medical equipment.
[0036] The present invention relates to Dissolving hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof to obtain a solution; and spray drying the resulting solution to obtain a hyaluronic acid composition.
[0037] In a particular preferred embodiment of the invention, the spray drying has an inlet temperature of 120-150° C. and an outlet temperature of 80-100° C., preferably with an atomization frequency of 30-50 Hz.
[0038] For spray drying, the inlet temperature may be, for example, 120° C., 125° C., 130° C., 135° C., 140° C., 145° C., 150° C., or any range therebetween; The exit velocity may be, for example, 80°C, 85°C, 90°C, 95°C, 100°C, or any range therebetween.
[0039] The atomization rate may be, for example, 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz, or any range therebetween.
[0040] In a specific preferred embodiment of the present invention, the hyaluronic acid composition obtained by spray drying is in the form of fine particles capable of passing through a 100 to 200 mesh.
[0041] The present invention provides a composition for promoting absorption of an active ingredient, comprising an active ingredient and the hyaluronic acid composition or a hyaluronic acid composition prepared by the preparation method.
[0042] The active ingredient may be an active ingredient known to a person skilled in the art, for example an active ingredient in the field of skin care products, an active ingredient in a pharmaceutical product, an active ingredient in a disinfectant product, an active ingredient in a dressing or an active ingredient in a gel medical device.
[0043] The gel medical device is a medical device used for oral nasal spray, repair gel, etc.
[0044] In certain preferred embodiments of the present invention, the active ingredient is a water-soluble active ingredient and / or an oil-soluble active ingredient.
[0045] The water-soluble active ingredient refers to an active ingredient that is soluble in water, and may be any water-soluble active ingredient for skin care products or gel medical devices known to those skilled in the art, such as tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene, or ectoine.
[0046] The oil-soluble active ingredient refers to an active ingredient that may be insoluble in water, and may be any oil-soluble active ingredient for skin care products or gel medical devices known to those skilled in the art, such as astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoyl phenylalanine, or ethylbisiminomethylguaiacol manganese chloride.
[0047] In a particular preferred embodiment of the present invention, the mass ratio of said active ingredient to said hyaluronic acid composition is 1:5 to 5:1, preferably 1:4 to 4:1.
[0048] For example, the mass ratio of the active ingredient to the hyaluronic acid composition (active ingredient / hyaluronic acid composition) is 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or any range therebetween.
[0049] The present invention provides use of the hyaluronic acid composition or a hyaluronic acid composition prepared by the above preparation method in improving absorption of an active ingredient, preferably, the active ingredient is a water-soluble active ingredient and / or an oil-soluble active ingredient.
[0050] In certain preferred embodiments of the present invention, the water-soluble active ingredient is tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene, or ectoine, and the oil-soluble active ingredient is astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoylphenylalanine, or ethylbisiminomethylguaiacol manganese chloride.
[0051] The present invention provides an article of manufacture comprising the composition.
[0052] In a preferred specific embodiment of the present invention, the hyaluronic acid composition is present in an amount of 0.1 to 2% by mass, preferably 0.5 to 1.5% by mass, as a weight percentage in the product.
[0053] For example, in a product, the hyaluronic acid composition may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2% by weight or any range therebetween.
[0054] In certain preferred embodiments of the invention, the product is a skin care product, a disinfectant product, a medicine, a dressing, or a gel medical device.
[0055] In certain preferred embodiments of the present invention, the skin care product is a toner, essence, cream, mask, lotion or other body care product.
[0056] In certain preferred embodiments of the present invention, the product further comprises other auxiliary materials, which may be any auxiliary materials known in the art, for example, the auxiliary materials of the skin care product may be butylene glycol, pentylene glycol, glycerin, caprylic / caprylic triglyceride, jojoba oil, hydrogenated lecithin, xanthan gum, carbomer, triethanolamine, poloxamer, tranexamic acid, astaxanthin, ethylparaben, etc.
[0057] The present invention provides use of the hyaluronic acid composition or the hyaluronic acid composition prepared by the preparation method in the field of products, and preferably, the hyaluronic acid composition is present in an amount of 0.1 to 2% by weight, preferably 0.5 to 1.5% by weight, in the product.
[0058] In certain preferred embodiments of the invention, the product is a skin care product, a disinfectant product, a medicine, a dressing, or a gel medical device.
[0059] In the present invention, the above-mentioned hyaluronic acid composition can be used to promote the absorption of active ingredients in products such as skin care products, medicines, disinfectant products, dressings or gel medical devices, and increase the percutaneous absorption rate of the active ingredients.
[0060] In the present invention, the materials and test methods used in the tests are generally and / or specifically described, and in the following examples, unless otherwise specified, % means wt%, i.e., weight percentage. Unless the manufacturer is specified, the reagents or equipment used are ordinary reagent products that can be purchased on the market.
[0061] [Table 1]
[0062] Example 1 20g of sodium hyaluronate with molecular weight of 400kDa, 10g of acetylated sodium hyaluronate with molecular weight of 100kDa, and 70g of hydrolyzed sodium hyaluronate with molecular weight of 18kDa were precisely weighed and mixed uniformly, then 1000ml of purified water was added to prepare a 10% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0063] Example 2 30g of sodium hyaluronate with molecular weight of 250kDa, 30g of acetylated sodium hyaluronate with molecular weight of 30kDa, and 40g of hydrolyzed sodium hyaluronate with molecular weight of 10kDa were precisely weighed and mixed uniformly, and then 2000ml of purified water was added to prepare a 5% aqueous solution, which was then processed by spray drying.The inlet temperature was set to 125℃, the outlet temperature to 90℃, and the atomizer frequency to 40Hz to obtain a uniform and fine powder.
[0064] Example 3 35g of sodium hyaluronate with molecular weight of 280kDa, 25g of acetylated sodium hyaluronate with molecular weight of 25kDa, and 40g of hydrolyzed sodium hyaluronate with molecular weight of 8kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0065] Example 4 25g of sodium hyaluronate with molecular weight of 300kDa, 20g of acetylated sodium hyaluronate with molecular weight of 30kDa, and 55g of hydrolyzed sodium hyaluronate with molecular weight of 5kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0066] Example 5 40g of sodium hyaluronate with molecular weight of 250kDa, 35g of acetylated sodium hyaluronate with molecular weight of 28kDa, and 45g of hydrolyzed sodium hyaluronate with molecular weight of 3kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0067] Example 6 30g of sodium hyaluronate with molecular weight of 210kDa, 20g of acetylated sodium hyaluronate with molecular weight of 20kDa, and 50g of hydrolyzed sodium hyaluronate with molecular weight of 3kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0068] Example 7 50g of sodium hyaluronate with a molecular weight of 150kDa, 15g of acetylated sodium hyaluronate with a molecular weight of 45kDa, and 35g of hydrolyzed sodium hyaluronate with a molecular weight of 3kDa were precisely weighed and mixed uniformly, and then 1000ml of purified water was added to prepare a 10% aqueous solution, which was then processed by spray drying.The inlet temperature was set to 120℃, the outlet temperature to 100℃, and the atomizer frequency to 50Hz to obtain a uniform and fine powder.
[0069] Example 8 55g of sodium hyaluronate with molecular weight of 300kDa, 15g of acetylated sodium hyaluronate with molecular weight of 10kDa, and 30g of hydrolyzed sodium hyaluronate with molecular weight of 15kDa were precisely weighed and mixed uniformly, and then 2000ml of purified water was added to prepare a 5% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 140℃, the outlet temperature at 80℃, and the atomizer frequency at 30Hz to obtain a uniform and fine powder.
[0070] Example 9 25g of sodium hyaluronate with molecular weight of 200kDa, 15g of acetylated sodium hyaluronate with molecular weight of 40kDa, and 60g of hydrolyzed sodium hyaluronate with molecular weight of 12kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set to 150℃, the outlet temperature to 80℃, and the atomizer frequency to 50Hz to obtain a uniform and fine powder.
[0071] Example 10 25g of sodium hyaluronate with molecular weight of 180kDa, 45g of acetylated sodium hyaluronate with molecular weight of 50kDa, and 30g of hydrolyzed sodium hyaluronate with molecular weight of 15kDa were precisely weighed and mixed uniformly, then 1000ml of purified water was added to prepare a 10% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 120℃, the outlet temperature at 100℃, and the atomizer frequency at 30Hz to obtain a uniform and fine powder.
[0072] Example 11 60g of sodium hyaluronate with molecular weight of 100kDa, 10g of acetylated sodium hyaluronate with molecular weight of 10kDa, and 30g of hydrolyzed sodium hyaluronate with molecular weight of 0.8kDa were precisely weighed and mixed uniformly, then 1000ml of purified water was added to prepare a 10% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0073] Example 12 20g of sodium hyaluronate with molecular weight of 500kDa, 50g of acetylated sodium hyaluronate with molecular weight of 80kDa, and 30g of hydrolyzed sodium hyaluronate with molecular weight of 20kDa were precisely weighed and mixed uniformly, then 1000ml of purified water was added to prepare a 10% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0074] Example 13 10g of sodium hyaluronate with molecular weight of 500kDa, 60g of acetylated sodium hyaluronate with molecular weight of 80kDa, and 30g of hydrolyzed sodium hyaluronate with molecular weight of 20kDa were precisely weighed and mixed uniformly, and then 2000ml of purified water was added to prepare a 5% aqueous solution, which was then processed by spray drying.The inlet temperature was set at 125℃, the outlet temperature at 90℃, and the atomizer frequency at 40Hz to obtain a uniform and fine powder.
[0075] Comparative Example 1 35 g of sodium hyaluronate with a molecular weight of 280 kDa, 25 g of acetylated sodium hyaluronate with a molecular weight of 25 kDa, and 40 g of hydrolyzed sodium hyaluronate with a molecular weight of 8 kDa were precisely weighed out, and the above three types of material powders were thoroughly mixed by stirring with a stirrer in preparation for use.
[0076] Comparative Example 2 35g of sodium hyaluronate with molecular weight of 280kDa and 25g of acetylated sodium hyaluronate with molecular weight of 25kDa are precisely weighed and mixed uniformly, then 3000ml of purified water is added to prepare a 3.33% aqueous solution, which is then processed by spray drying.The inlet temperature is set to 125℃, the outlet temperature is set to 90℃, and the atomizer frequency is set to 40Hz, to obtain a uniform and fine powder.
[0077] Comparative Example 3 35g of sodium hyaluronate with molecular weight of 280kDa and 40g of hydrolyzed sodium hyaluronate with molecular weight of 8kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying. The inlet temperature was set to 125℃, the outlet temperature to 90℃, and the atomizer frequency to 40Hz, to obtain a uniform and fine powder.
[0078] Comparative Example 4 25g of acetylated sodium hyaluronate with molecular weight of 25kDa and 40g of hydrolyzed sodium hyaluronate with molecular weight of 8kDa were precisely weighed and mixed uniformly, then 3000ml of purified water was added to prepare a 3.33% aqueous solution, which was then processed by spray drying.The inlet temperature was set to 125℃, the outlet temperature to 90℃, and the atomizer frequency to 40Hz to obtain a uniform and fine powder.
[0079] [Table 2]
[0080] Experimental Example 1 Solubility 2.0 g of each of the powders obtained in Examples 1 to 13 and Comparative Examples 1 to 4 was weighed into a 250 ml beaker, purified water at 25° C. was added, and the mixture was stirred at a stirring speed of 300 rpm. The time required for complete dissolution was recorded, and the results are shown in Table 3.
[0081] [Table 3]
[0082] As is clear from Table 3, the compositions obtained in Examples 1 to 13 have excellent solubility and have a dissolution time of less than 25 minutes, while the compositions obtained in Comparative Examples 1 to 4 have a long dissolution time of 29 minutes or more, and the compositions of the present invention have excellent solubility.
[0083] Experimental example 2: Particle size detection Approximately 10 g of each of the samples of Examples 1 to 13 and Comparative Examples 1 to 4 was designated as W0, which was sieved through a 200 mesh standard sieve. The samples that passed through the sieve were collected and weighed to be designated as W1, where the passing rate = W1 / W0 × 100% by weight, and the results are shown in Table 4.
[0084] [Table 4]
[0085] As is clear from Table 4, when the compositions obtained in Examples 1 to 13 were sieved through a 200 mesh sieve, the passing rate was 85% or more, indicating that the particle diameter of the obtained compositions was small and uniform in size, while the passing rate of the comparative examples was 83% by weight or less, indicating that the compositions of the present invention have small and uniform particle diameters.
[0086] Experimental Example 3: Absorption evaluation The compositions obtained in Examples 1 to 13 and Comparative Examples 1 to 4 were used to prepare 2% aqueous solutions, and 0.25 ml of each sample was applied to the skin of the inner arm of a volunteer in an area of 4 cm x 4 cm. During application, the volunteer recorded and evaluated the time required for the sample to be completely absorbed through subjective sensation. The experimental results are shown in Table 5.
[0087] [Table 5]
[0088] As is clear from Table 5, the compositions obtained in Examples 1 to 13 had a high absorption rate, with the time required for complete absorption being 24 seconds or less, while the compositions described in Comparative Examples 1 to 4 had a time required for complete absorption being 26 seconds or more, indicating that the compositions described in the present invention have a high absorption rate.
[0089] Application Examples Study of percutaneous absorption In order to observe whether a hyaluronic acid composition having a penetration enhancing effect has a percutaneous absorption enhancing effect on the target substances (tranexamic acid and astaxanthin), the following experiment was carried out.
[0090] Application verification example 1 Formulations containing tranexamic acid are shown below.
[0091] [Table 6]
[0092] Experimental steps 1. Tranexamic acid content methodology 1.1 Establishment of HPLC detection method 1.1.1 Chromatographic conditions Chromatography column: Hypersil C18 column (150 mm x 4.6 mm, 5 μm) Mobile phase: 0.23% sodium dodecyl sulfate solution-methanol (60:40, V / V) Preparation of 0.23% sodium dodecyl sulfate solution: 18.3 g of sodium dihydrogen phosphate was dissolved in 800 ml of water, 8.3 ml of triethylamine was added and mixed uniformly, 2.3 g of sodium dodecyl sulfate was added, and the mixture was dissolved by shaking. The pH value was adjusted to 2.5 with phosphoric acid, and water was added until the total volume was 1000 ml, and the mixture was shaken uniformly. Flow rate: 0.8ml / min Column temperature: 35℃ Detection wavelength: 220nm Injection volume: 20μl
[0093] 1.1.2 Linear Relationship Investigation 2.0059 g of tranexamic acid control sample was precisely weighed and diluted to 100 ml with mobile phase for use. Appropriate amounts of stock solution were transferred and diluted with mobile phase to prepare standard working solutions with concentrations of 0.01, 0.01, 0.1, 1, 5, 10, and 20 mg / ml. 20 μL was taken and the peak area (A) at 220 nm for each group was measured by HPLC, and a linear regression was performed on the A value for concentration (ρ) to calculate the calibration curve. Here, the results of the linear relationship investigation are shown in FIG. 1, with the peak area (A) on the vertical axis and the mass concentration of tranexamic acid (μg / ml) on the horizontal axis. From Figure 1, it is clear that the linear regression equation is y=429.57x-0.8027, r 2 = 1, and tranexamic acid showed good linearity with the peak area at 1 to 20 mg / ml.
[0094] 1.2 Evaluation of in vitro percutaneous absorption 1.2.1 In vitro penetration experiments The abdominal skin of SD rats was taken (rats were purchased from Qinglongshan Animal Breeding Farm, Jiangning District, Nanjing, and the abdominal skin was removed by the rats themselves in the laboratory), and after removing tissues such as fat, muscle, and mucosa, they were sandwiched between Franz diffusion cells and treated with a 32°C water bath. The control group's feed cell was given 1ml of the control solution, and the sample group's feed cell was given 1ml of the verification formula at the same concentration. An appropriate amount of saline was added to the receiving cell and stirred at 400r / min. 5ml was sampled from the receiving cell at 0.5, 1.0, 2.0, 4.0, 6.0, 8.0, 12.0, and 24.0h, respectively, and 5ml of saline was replenished at the same time. The obtained sample solution was filtered through a 0.22 microporous filtration membrane, and then detected under the chromatographic conditions described in 1.1.1, and substituted into the regression equation to obtain the mass concentration of the drug. The cumulative transmission amount per unit area (Qn) was calculated from the mass concentration of the sample at each sampling point according to the following formula, and the calculation results are shown in Figure 2.
[0095]
number
[0096] Cn and Ci are the drug mass concentrations (μg / ml) measured at the nth and ith sampling points, respectively, V and V0 are the volume of the receiving cell and the sampling volume (ml), respectively, and A is the permeation area (cm 2 ).
[0097] As can be seen from Figure 2, in the control formulation, the cumulative permeation rate of tranexamic acid over 24 hours was (24.3±14.9)μg / cm 2 In the experimental formulation, the cumulative 24-h permeation rate of tranexamic acid was (92.2±23.3)μg / cm 2 This was about 4 times that of the control formulation, and the difference between the groups was highly significant (t-test, P<0.01). Since the difference between the two formulations was only in the hyaluronic acid composition, it was suggested that the addition of the hyaluronic acid composition of Example 6 to the formulation as a transdermal delivery carrier significantly promoted the transdermal absorption of tranexamic acid.
[0098] 1.2.2 Ex vitro retention experiments The abdominal skin of SD rats was taken, and after removing tissues such as fat, muscle, and mucous membrane, it was sandwiched between the middle of a Franz diffusion cell and treated with a 32 ° C water bath. The control group's feeding cell was given 1 ml of the control solution, and the sample group's feeding cell was given 1 ml of the same concentration of the verification formula. An appropriate amount of saline was added to the receiving cell and stirred at 400 r / min. The skin tissue was taken out at 2.0, 4.0, 6.0, 12.0, and 24.0 h, respectively, and the residual drug on the skin surface was washed, sucked with filter paper and dried, and the effectively permeated skin was cut out, added with 5 ml of methanol-water (40:60), crushed with a tissue grinder for 2 min, extracted with ultrasound for 30 min, and 2 ml of the supernatant was taken and centrifuged at 12000 r / min for 10 min. The obtained sample solution was filtered through a 0.22 microporous filtration membrane, and then detected under the chromatographic conditions described in 1.1, and substituted into the regression equation to determine the mass concentration of the drug, and the retention amount was calculated, and the results are shown in Figure 3. As can be seen from Figure 3, in the test formulation group, the amount of tranexamic acid retained in the skin reached a maximum of 153.12 μg / cm at 2 h. 2 This was higher than that of the control group, indicating that when the hyaluronic acid composition of Example 6 was added, tranexamic acid was rapidly retained in the epidermal layer of the skin, which was advantageous for percutaneous absorption at a later time.
[0099] 1.2.3 Hydration experiment Skin hydration is the ability of keratin or its decomposition products in the outer layer of the skin to bind with water, and the degree of hydration is the amount of water in the stratum corneum. Hydration increases the amount of water in the stratum corneum of the skin, softening the tissue and filling the keratinocytes, increasing the amount of water in the gaps between the cells and enlarging the gaps, promoting the percutaneous penetration of active ingredients. The volunteers first washed the insides of their forearms with purified water, and after 30 minutes, pressed the moisture measurement probe vertically against the surface of the skin to be measured, adjusting the pressure according to the display on the device's screen until the measurement result was displayed, and then applied the sample to be measured. After 30 minutes, the hydration degree was measured again, and the hydration improvement rate was calculated according to the formula.
[0100]
number
[0101] Here, H is the hydration improvement rate, H 1 is the degree of hydration measured after sample application, H 0 is the degree of hydration measured before sample application. The calculated improvement in hydration degree was 78.61%.
[0102] Application verification 2: Examination of in vitro penetration experiments, ex vitro retention experiments, and hydration degree experiments of other examples and comparative examples For the hyaluronic acid compositions obtained in Examples 1 to 5, Examples 7 to 13, and Comparative Examples 1 to 4, experiments were conducted according to the method described in Application Verification 1, and the results of the cumulative permeation amount, skin retention amount, and hydration degree are shown in Table 7.
[0103] [Table 7]
[0104] From Table 7, it is clear that in the verification formulas formulated with the hyaluronic acid compositions described in Examples 1-5 and Examples 7-13, the cumulative permeation amount and skin retention amount are both high, and the improvement rate of hydration degree is also high, because the hyaluronic acid or its salt in the hyaluronic acid composition of Examples has excellent moisturizing effect, and acetylated hyaluronic acid or its salt promotes skin hydration, which makes tissue soft, keratinocytes full, increases the water content in the intercellular space, opens the skin barrier, and allows free nutrients, hydrolyzed hyaluronic acid or its salt, and nutrients bound with hyaluronic acid or its salt to enter the skin, promoting the absorption of active ingredients.From this, it is shown that the hyaluronic acid composition described in Examples can promote the rapid permeation of tranexamic acid into the skin and retention in the epidermis layer, which is favorable for subsequent percutaneous absorption, and thus the hyaluronic acid composition described in the present invention can promote the absorption of active ingredients.
[0105] Application verification 3 Formulations containing astaxanthin are shown below.
[0106] [Table 8]
[0107] 1. Materials and Methods 1.1 Establishment of HPLC detection method 1.1.1 Chromatographic conditions Chromatography column: Hypersil C18 column (150 mm x 4.6 mm, 5 μm) Mobile phase: methanol-water (95:5, V / V) Flow rate: 1.0ml / min Column temperature: 25℃ Detection wavelength: 475nm Injection: 20μL
[0108] 1.1.2 Preparation of calibration curve 5.0 mg of astaxanthin control sample was precisely weighed, 1 ml of dichloromethane was added, and the solution was diluted to 50 ml with methanol and stored at -4°C in the dark for use. An appropriate amount of stock solution was taken and diluted with methanol to obtain standard working solutions with concentrations of 0.5, 1.0, 2.0, 5.0, 10.0, and 20.0 μg / ml. When used, 20 μL was taken and the peak area (A) at 475 nm of each group was measured by HPLC, and a linear regression was performed on the concentration (ρ) with the A value to calculate the calibration curve. Here, the results of the linear relationship investigation are shown in FIG. 4, with the peak area (A) on the vertical axis and the mass concentration of astaxanthin (μg / ml) on the horizontal axis. As can be seen from Figure 4, the linear regression equation is y=151.75x+26.752, r 2 =0.9991, and astaxanthin showed good linearity with the peak area at 0.5 to 20 μg / ml.
[0109] 1.2 Evaluation of in vitro percutaneous absorption 1.2.1 Preparation of control solutions for in vitro evaluation 1 g of hydroxyethyl cellulose (HEC) was dissolved in 80 ml of water, left to swell, and stirred uniformly for use. 0.1200 g of astaxanthin oil and 6.0 mg of standard astaxanthin were each uniformly dispersed in 5 g of glycerin, then added to the HEC gel, and then diluted to 100 ml with water.
[0110] 1.2.2 Ex vitro retention experiments The abdominal skin of SD rats was taken, and after removing tissues such as fat, muscle, and mucosa, it was sandwiched between the Franz diffusion cells and treated with a 32℃ water bath. The control group's feed cells were each given 1ml of two types of control solution, the sample group's feed cells were given 1ml of the same concentration of sample, and the receiving cells were given an appropriate amount of 1% Tween 80 solution and stirred. The tissues were taken out at 2.0h, 4.0h, 6.0h, 12.0h, and 24.0h, respectively, and the surface residues were washed five times with physiological saline, sucked and dried with filter paper, and the effectively permeated skin was cut out, added with 4ml of solvent (methanol: dichloromethane 3:1), crushed with a tissue grinder for 2min, extracted with ultrasound for 30min, added with 1ml of 1% KOH methanol solution, shook well, reacted at 30℃ for 30min, centrifuged at 5000r / min under 4℃ conditions for 5min, filtered through a 0.22μm filter membrane, and the average data are shown in Table 9.
[0111] [Table 9]
[0112] As can be seen from Table 9, the control formulation group and the test formulation group had a 24-h whole face retention of 0.011 μg / cm, respectively. 2 and 0.038 μg / cm 2 There was a significant difference in the retention amount between the two groups, and the only difference between the two groups was the difference in the content of the hyaluronic acid composition (the test formulation contained 0.4% hyaluronic acid composition, and the control formulation contained no hyaluronic acid), so it is believed that the hyaluronic acid composition of Example 6 played an important role in the percutaneous absorption of astaxanthin.
[0113] 1.2.2 Hydration experiment Skin hydration is the ability of keratin or its decomposition products in the outer layer of the skin to bind with water, and the degree of hydration is the amount of water in the stratum corneum. Hydration increases the amount of water in the stratum corneum of the skin, softening the tissue and filling the keratinocytes, increasing the amount of water in the gaps between the cells and enlarging the gaps, promoting the percutaneous penetration of active ingredients. The volunteers first washed the insides of their forearms with purified water, and after 30 minutes, pressed the moisture measurement probe vertically against the surface of the skin to be measured, adjusting the pressure according to the display on the device's screen until the measurement result was displayed, and then applied the sample to be measured. After 30 minutes, the hydration degree was measured again, and the hydration improvement rate was calculated according to the formula.
[0114]
number
[0115] Here, H is the hydration improvement rate, H 1 is the degree of hydration measured after sample application, H 0 is the degree of hydration measured before sample application. The obtained hydration improvement rate was 86.44%.
[0116] Application Verification 4: Examination of Ex Vitro Retention Experiments and Hydration Degree Experiments of Other Examples and Comparative Examples The hyaluronic acid compositions obtained in Examples 1 to 5, Examples 7 to 13, and Comparative Examples 1 to 4 were subjected to experiments according to the method described in Application Verification 3. The results of the skin retention amount and hydration degree are shown in Table 10.
[0117] [Table 10]
[0118] From Table 10, it is clear that when the hyaluronic acid composition described in the embodiment is used, the skin retention amount within 24h is significantly different from that of the comparative example, and it is shown that the hyaluronic acid composition described in the embodiment can promote the percutaneous absorption of astaxanthin.In addition, the improvement rate of hydration degree is also significantly different from that of the comparative example, and hydration degree represents the amount of water content of the stratum corneum, so that the water content of the stratum corneum of the skin increases due to hydration, the tissue becomes soft, the keratinocytes are filled, the water content of the intercellular space increases, the gap becomes larger, and the percutaneous penetration of active ingredient is promoted, and this shows that the hyaluronic acid composition described in the present invention can promote the absorption of active ingredient.
[0119] From the above, the present invention adopts hyaluronic acid composition, hyaluronic acid or its salt corresponds to a very small net-like structure, and is distributed on the surface layer of the skin; acetylated hyaluronic acid or its salt has acetyl, so it has lipophilicity and affinity with skin, and forms a channel; hydrolyzed hyaluronic acid or its salt can penetrate quickly to the skin layer through the channel of acetylated hyaluronic acid or its salt; hydrolyzed hyaluronic acid or its salt can be mixed with hyaluronic acid or its salt to quickly open the barrier of the skin, so that free nutrients, hydrolyzed hyaluronic acid or its salt and nutrients combined with hyaluronic acid or its salt can enter the skin, and promote the absorption of active molecules.In addition, said hyaluronic acid composition can improve hydration, soften tissue, fill keratinocytes, increase the water content in the gap between cells, and enlarge the gap, which is favorable for the percutaneous penetration of active ingredients.
[0120] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms, and those skilled in the art can use the technical content disclosed above to change or modify the above into equivalent embodiments with equivalent changes. However, if it does not deviate from the content of the technical solution of the present invention, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention also belongs to the patent scope of the technical solution of the present invention.
Claims
1. Hyaluronic acid or a salt thereof; Acetylated hyaluronic acid or a salt thereof; A hyaluronic acid composition comprising hydrolyzed hyaluronic acid or a salt thereof, As a weight percentage in the hyaluronic acid composition, The hyaluronic acid or its salt is 25 to 55% by weight, The acetylated hyaluronic acid or its salt is 15 to 35% by weight, The hydrolyzed hyaluronic acid or salt thereof is 30-60% by weight; The molecular weight of the hyaluronic acid or its salt is 150 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or its salt is 10 kDa to 50 kDa. A hyaluronic acid composition, wherein the molecular weight of the hydrolyzed hyaluronic acid or its salt is 3 kDa to 15 kDa.
2. The hyaluronic acid composition according to claim 1, comprising hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof.
3. Dissolving hyaluronic acid or a salt thereof, acetylated hyaluronic acid or a salt thereof, and hydrolyzed hyaluronic acid or a salt thereof to obtain a solution; and spray drying the resulting solution to obtain a hyaluronic acid composition. As a weight percentage in the hyaluronic acid composition, The hyaluronic acid or its salt is 25 to 55% by weight, The acetylated hyaluronic acid or its salt is 15 to 35% by weight, The hydrolyzed hyaluronic acid or salt thereof is 30-60% by weight; The molecular weight of the hyaluronic acid or its salt is 150 kDa to 300 kDa. The molecular weight of the acetylated hyaluronic acid or its salt is 10 kDa to 50 kDa. The molecular weight of the hydrolyzed hyaluronic acid or its salt is 3 kDa to 15 kDa. A method for preparing a hyaluronic acid composition.
4. The method according to claim 3, wherein the total amount of the hyaluronic acid or its salt, the acetylated hyaluronic acid or its salt, and the hydrolyzed hyaluronic acid or its salt is 1 to 10 mass% relative to the solution.
5. The method according to claim 3, wherein in the spray drying, the inlet temperature is 120-150°C and the outlet temperature is 80-100°C.
6. The method according to claim 3, wherein the atomization frequency is 30 to 50 Hz.
7. A composition for promoting absorption of an active ingredient, comprising an active ingredient and the hyaluronic acid composition described in claim 1 or 2, wherein the active ingredient is a water-soluble active ingredient and / or an oil-soluble active ingredient.
8. The composition described in claim 7, wherein the water-soluble active ingredient is tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene or ectoine, and the oil-soluble active ingredient is astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoyl phenylalanine or ethylbisiminomethylguaiacol manganese chloride.
9. The composition described in claim 7, wherein the mass ratio of the active ingredient to the hyaluronic acid composition is 1:5 to 5:
1.
10. The composition described in claim 7, wherein the mass ratio of the active ingredient to the hyaluronic acid composition is 1:4 to 4:
1.
11. A hyaluronic acid composition as described in claim 1 or 2 for use in improving absorption of an active ingredient, wherein the active ingredient is a water-soluble active ingredient and / or an oil-soluble active ingredient.
12. The composition according to claim 11, wherein the water-soluble active ingredient is tranexamic acid, nicotinamide, vitamin C, ergothioneine, a low molecular weight peptide containing 2 to 10 amino acids, aminobutyric acid, deoxyribonucleic acid, proxylene, or ectoine, and the oil-soluble active ingredient is astaxanthin, salicylic acid, ferulic acid, phenylethyl resorcinol, resveratrol, undecylenoyl phenylalanine, or ethylbisiminomethylguaiacol manganese chloride.
13. 9. An article of manufacture comprising the composition of claim 7 or 8.
14. The product described in claim 13, wherein the hyaluronic acid composition is present in an amount of 0.1 to 2% by weight of the product.
15. The product described in claim 13, wherein the hyaluronic acid composition is 0.5 to 1.5 mass% of the product.
16. 14. The product of claim 13, wherein the product is a skin care product, a disinfectant product, a medicine, a dressing, or a gel medical device.
17. The product of claim 16, wherein the skin care product is a toner, essence, cream, mask or lotion.
18. Use of the hyaluronic acid composition according to claim 1 or 2 or the hyaluronic acid composition prepared by the preparation method according to any one of claims 3 to 6 in the field of products.
19. The use described in claim 18, wherein the hyaluronic acid composition is present in an amount of 0.1 to 2% by weight in the product.
20. The use described in claim 18, wherein the hyaluronic acid composition is present in an amount of 0.5 to 1.5% by weight in the product.
21. The use of claim 18, wherein the product is a skin care product, a disinfectant product or a dressing.
Citation Information
Patent Citations
Moisturizing essence lotion and preparation method thereof
CN106109296A
Hyaluronic acid skin care film, preparation method and application
CN106176286A
Hyaluronic acid stoste and preparation method thereof
CN109730953A
Diversified functional compound composition containing hyaluronic acid or salt thereof and application of composition
CN111686033A
Preparation for external use for skin
JP1998279421A